World Climate Research Programme lighthouse activity: an assessment of major research gaps in solar radiation modification research - Haywood, Jim M.; Boucher, Olivier; Lennard, Chris; Storelvmo, Trude; Tilmes, Simone; Visioni, Daniele (Frontiers in Climate, 2025)
It is increasingly evident that maintaining global warming at levels below those agreed in the legally binding international treaty on climate change. i.e., the Paris Agreement, is going to be extremely challenging using conventional mitigation techniques. While future scenarios of climate change frequently include extensive use of terrestrial and marine carbon dioxide removal in the second part of the 21st century, it is unproven that these techniques can be scaled-up to reach the scale required to significantly reduce concentrations of atmospheric carbon dioxide and significant uncertainties and detrimental side-effects exist. These issues have led to increasing interest in so-called “Solar Radiation Modification” whereby the global mean temperature of the Earth is reduced by either blocking a small fraction of sunlight from reaching it or by increasing the Earth’s albedo to reflect a small proportion of incident sunlight back out to space. Here we systematically identify key research gaps associated with the two most prominent Solar Radiation Modification techniques, i.e., Stratospheric Aerosol Injection (SAI) and Marine Cloud Brightening (MCB). We provide an assessment of the research gaps associated with other less prominent SRM techniques. We assert that transparency and inclusivity in SRM research is essential in providing objective and impartial research findings to each and every stakeholder in an equitable way.